Evaluation of In Vivo Properties of Velosorb™ Fast Versus Vicryl™ Rapide in a Functional Rabbit Model of Intradermic Suture and Episiotomy. (1st April 2015) - Vieille, P.; Huberlant, S.; Bastide, S.; Bayon, Y.; de Tayrac, R.
ABSTRACT Objective: Fast-absorbing polyglactin 910 is commonly used to suture skin and vaginal incisions. In vitro studies have shown similar tensile strength properties between Velosorb™ Fast and Vicryl™ Rapide (Al-Qattan MM. J Hand Surg Br Eur. 2005;30(1):90–91). This randomized study compared Velosorb™ Fast (Covidien) with Vicryl™ Rapide (Ethicon) in a rabbit model of intradermic suture and episiotomy. Materials and Methods: This randomized prospective study was performed on 20 New Zealand rabbits, in which we realized a mediolateral perineo-vaginal incision and two vertical skin incisions of about 8 cm on the abdominal wall. The sutures were randomized between Velosorb™ Fast (Covidien) and Vicryl™ Rapide (Ethicon), and each rabbit was treated with the same suture on both vaginal incision and left abdominal incision, while the right abdominal incision was closed with an alternate suture. A macroscopic examination was performed on days 5 and 11. On day 11, animals were sacrificed for histological (Badylak quantitative score) and electron microscopic examinations. Differences were considered significant at p < .05. Results: All of the rabbits survived and were included in the final results. Fifty-one sutures were visible by histologic analysis (27 in the Velosorb™ Fast group and 24 in the Vicryl™ Rapide group). The power of the study was ≥80%. There was no significant difference between the two groups based on the total histologic Badylak score analysis or the Badylak sub-score analysis. Conclusions: Velosorb™ Fast seems to be as efficient as Vicryl™ Rapide for use in perineal and skin closure.